Refractive Surgery Survey 2004 - Sandoval, Helga P.; de Castro, Luis E. Fernández; Vroman, David T.; Solomon, Kerry D. (Journal of cataract and refractive surgery, 2005)
To determine the refractive surgery (RS) preferences of ophthalmologists worldwide, questionnaires were sent to 8897 members of the American Society of Cataract and Refractive Surgery. A total of 1053 questionnaires were returned by the deadline. The practice distribution included 29.5% cataract surgeons, 48.8% comprehensive ophthalmologists, 11.6% RS specialists, 5.1% cornea and external disease specialists, 1.9% glaucoma specialists, 1.1% retina specialists, and <1.0% oculoplastics/pediatrics/researchers/retired. Results were compared with those in the 2003 survey and demonstrate that refractive surgery continues to develop and change.